Symbolic Interaction in Sociocultural Settings: Human Hand as a Universal Symbol - Trako, Tijana (2010)
Symbols always held a crucial place in the complex network of information transfer, as humans formed groups, communities and societies. Among the symbols most exploited from the very beginnings of culture were the symbols of human body. However, not all parts of the human body are equally represented in symbolic interaction. From the earliest evidence of human existence (e.g. cavemen handprints), one organ held a special place in human imagination – the human hand. The significance of this symbol did not change through history, and it was used in a variety of sociocultural settings: religion, politics, arts and everyday communication. The paper will analyze the use of human hand that appears as a universal symbolic object, but which takes on different meanings attributed within different social and cultural settings. G. H. Mead (1934), giving the example of a raised fist, recognized the importance of the hand as a “significant symbol“. The aim of the paper is to give a novel contribution to the research of social symbolism by applying Mead’s and other relevant theoretical concepts in symbolic interaction theory, as well as some phenomenological and other sociological contributions (Durkheim, Parsons, Berger and Luckmann, Goffman, etc.), by looking at a particular symbol.
Projekt MZOS
ENG